Modelling for Estimation Carbon Stocks in Land Cover Using A System Dynamic Approach (Case Study: Prabumulih City, South Sumatera, Indonesia) - Yuniar Pratiwi; Amin Rejo; Armina Fariani; Muhammad Faizal (Institut Pertanian Bogor (IPB University), 2022)
Human activities, which have interfered with the ecological system, have led to global warming. This has led to the release of carbon stocks into the atmosphere, thereby reducing the function of carbon sinks in places with vegetated land. With increased human activities, vegetated land will soon become non-vegetated. This is because the increased human activities have led to the absorption of higher amounts of carbon in the atmosphere than the required level. Therefore, this study aimed to estimate land cover on carbon stocks in Prabumulih City, South Sumatera Province, Indonesia. The study employed a random field survey using a dynamic system, with the results showing that land cover consisted of oil palm plantations, mixed plantations, grass, swamp shrubs, and rivers. However, the area was dominated by rubber plantations, and as a result, the carbon stocks continued to decline. For instance, in 2008, the level of carbon stock was 2,438.72 Gg and fell to 2,190.85 Gg in 2020, indicating a 4.8% decrease. It is projected that by 2030, the carbon stock in land cover will be 1,988.07 Gg.